Design of a Workshop Training Course based on the Sufficiency Economy Philosophy for Sustainable Electricity use for Provincial Electricity Authority Employees - Rungruang, Thanachai; Tanitteerapan, Tanes; Jitgarun, Kalayanee; Sunthonkanokpong, Wisuit; Leekitchwatana, Punnee (International Journal of Educational Communications and Technology, 2025)
The study aimed to assess the effectiveness of a workshop training course on social innovation or the sufficiency economy (SEP) principles for sustainable innovation (SI) of sustainable electricity use among provincial electricity authority personnel. The results revealed that the quality of the content (M = 4.78, SD = 0.58) and the media (M = 4.50, SD = 0.58) of a workshop training course based on the SEP for sustainable electricity use of provincial electricity authority personnel by the 9 experts was at the greatest level. The design of a workshop training course based on SEP for SI of sustainable electricity use for provincial electricity authority personnel to enhance learning achievement was efficient by E1/E2 (82.40/81.33) by the specified hypothesis 80/80. The significant difference between pretest (M = 14.44, SD = 0.88) and posttest (M =16.11, SD = 1.05) scores of a workshop training course based on SEP for SI of sustainable electricity use for provincial electricity authority personnel were at the 0.01 level. Then, the provincial electricity authority personnel’s satisfaction with a workshop training course based on the SEP for sustainable electricity use was at the highest level (M =4.90, SD = 0.12)